A comprehensive review of the relationship between autophagy and sorafenib-resistance in hepatocellular carcinoma: ferroptosis is noteworthy - Zhang, Kangnan; Zhang, Qinghui; Jia, Rongrong; Xiang, Shihao; Xu, Ling (Frontiers in Cell and Developmental Biology, 2023)
Patients with hepatocellular carcinoma (HCC) bear a heavy burden of disease and economic burden but have fewer treatment options. Sorafenib, a multi-kinase inhibitor, is the only approved drug that can be used to limit the progression of inoperable or distant metastatic HCC. However, enhanced autophagy and other molecular mechanisms after sorafenib exposure further induce drug resistance in HCC patients. Sorafenib-associated autophagy also generates a series of biomarkers, which may represent that autophagy is a critical section of sorafenib-resistance in HCC. Furthermore, many classic signaling pathways have been found to be involved in sorafenib-associated autophagy, including the HIF/mTOR signaling pathway, endoplasmic reticulum stress, and sphingolipid signaling, among others. In turn, autophagy also provokes autophagic activity in components of the tumor microenvironment, including tumor cells and stem cells, further impacting sorafenib-resistance in HCC through a special autophagic cell death process called ferroptosis. In this review, we summarized the latest research progress and molecular mechanisms of sorafenib-resistance-associated autophagy in detail, providing new insights and ideas for unraveling the dilemma of sorafenib-resistance in HCC.